A Taste Preference Study in Pediatric Patients: Paracetamol and Ibuprofen - Elif Aksöz; Selçuk Yazıcı; Oğuzhan Korkut; Nebahat Yılmaz; Tanju Çelik (Galenos Publishing House, 2019)
INTRODUCTION: Ibuprofen and paracetamol are two of the most commonly used medicines to treat fever in children. In pediatric patients, good taste is the most important factor for completing treatment. Taste preferences might be different in children from different cultures and countries. The aim of this study is to detect which preparations of paracetamol and ibuprofen are preferred in terms of taste and smell in outpatient children in Turkey. METHODS: In this study, two different paracetamol and two different ibuprofen liquid formulations were evaluated. The study population consisted of 145 children (71 girls, 74 boys) with a complaint of fever at a mean age of 5.69 +-2.93 years. A questionary was prepared for assessing the demographic variables and compliance and a '5-point facial hedonic scale' was added to the form for evaluating the taste and smell of drugs by children. After the end of treatment parents fill out the entire form and to bring it back bring it back during the check-up examination. RESULTS: There was no statistically significant difference between the taste and smell preference of different paracetamol or ibuprofen preparations. However, the increase in taste and smell scores was accompanied with a significant decrease for the need of additional nutrients and spitting behavior. DISCUSSION AND CONCLUSION: There was no statistically significant difference between the taste and smell preference of different paracetamol or ibuprofen preparations. However, the increase in taste and smell scores was accompanied with a significant decrease for the need of additional nutrients and spitting behavior.